Assessing status and habitat of siamese fireback (Lophura diardi) by using camera trap in Lo Go-Xa Mat National Park, Vietnam - Vy, Nguyen Tran; Quang, To; Long, Ho Dac; Hai, Hoang Van; Phuong, Huynh Huy; Dien, Nguyen Long; Tan, Nguyen Minh (Academia Journal of Biology, 2020)
Siamese fireback, Lophura diardi, belonging to Galliformes is at risk due to habitat loss and hunting, which are main challenges to conservation of the species. In order to provide scientific information to conserve the L. diardi, we implemented a camera-trap survey in Lo Go-Xa Mat National Park from 2017 to 2018. Occupancy and Poisson regression models were used to investigate presence of the species and potential factors influencing the occurrence of the species in the study area. Our results showed that the probability of occurrence of the species at locations within the park was high at 0.84 (0.69–0.92) and detection probability was relative low at 0.19 (0.16–0.23). The best models consistently suggested that the abundance of the species was high in closed canopy forest cover (β = 0.41), but appeared to be notably lower in areas far away from the ranger stations (β = -0.25) and in places with high frequency of human (β = -0.22). This research provided the first quantitative information of status and potential factors influencing occurrence of the L. diardi in the park, which is an essential data for developing practical actions to protect the species and monitoring program in the future for the park.